ANALISIS PENERAPAN SISTEM ENTERPRISE RESOURCE PLANNING(ERP) PADA PROSES PRODUKSI SHOELAST DI PT YIN HWA INDONESIA - Asep Rahmatullah; Bayu Kiswantoro (LPPM Universitas Bina Bangsa, 2021)
PT Yin Hwa Indonesia is a company that produces Shoelasts which will be used to support the production of shoes with world-famous brands. Based on the data obtained by researchers from the ERP system there are differences that occur between conditions in the field and data stored in the ERP system. This difference condition is getting bigger when the production of shoelast has exceeded 20000 pairs every month.The purpose of this study is to analyze the implementation of the ERP system in the Shoelast Production Process and to find solutions related to the problems of implementing the ERP system so that problems regarding the application of the ERP system are no longer found.The research method used is the PDCA method, which is the method used to solve the problem of data differences in the ERP system that occurs in the production department.Observations and interviews conducted by researchers, there are several problems that must be taken corrective action, namely making SOPs due to the absence of SOPs related to the implementation of ERP systems in the production section, increasing bandwidth because ERP systems that use internet networks require a capacity that matches the number of ERP system users, worker training in order to improve competence in running an ERP system in the production section ， and it is necessary to install additional software, namely Lan Messengger to support the speed of information between the recipient of information from consumers and the part that runs the information.From the observations, it can be suggested that improvements that need to be implemented by the company include making SOPs with ISO 9001: 2015 standards, increasing bandwidth, training workers and installing the Lan Messengger software